Peran self control sebagai mediasi literasi keuangan dan kesejahteraan keuangan wanita karir - Rizki Ayu Arilia; Wiwik Lestari (Universitas Hayam Wuruk Perbanas, 2022)
The purpose of this research was to examine the effect of financial literacy, income level, and lifestyle on career women well-being. This study also tested self-control as mediation variable. By using purposive sampling technique, there are 228 respondents who meet the characteristics of career women who financially independent, living in the five big cities in East Java. All respondents filled an online survey, which is contained valid and reliable instrument. The test was done by partial least squares (PLS). The results indicate that financial literacy has no significant effect on financial well-being, income level has a positive and significant effect on financial well-being, lifestyle has a significant negative effect on financial well-being and self-control mediates the effect of financial literacy on financial well-being. This result implies that literacy it self cannot affect on well being otherwise increase self control that in turn can support the intention to reach of higher level of well-being.